BURNOUT PROFILE OF ELEMENTARY SCHOOL TEACHER EDUCATION STUDENTS (ESTES): FACTORS AND IMPLICATION OF GUIDANCE AND COUNSELING SERVICES - Mubiar Agustin; Ruli Setiyadi; Ryan Dwi Puspita (IKIP Siliwangi, 2020)
This study departs from the discovery of the phenomenon of the burnout of learning experience of students, especially those who are already in the fourth or fifth semester of lecture activities. Symptoms of burnout experienced by students are in four areas, namely physical, emotional, intellectual, and low motivation. This study aims to find the profile of students' learning burnout, the underlying factors and their implications for guidance services. The method in this study uses a quantitative approach with descriptive analytic. The sample in this study was 53 randomly assigned ESTES. The instrument used in this study was a questionnaire to capture data about the learning burnout profile and also the underlying factors. The results showed that 60.38% of students experienced high levels of learning burnout and the rest were low. Based on the analysis, the factors that cause students' learning burnout as a result of the study show that the factors that are at a high rate are not able to accept if the grades are not in line with expectations and not confident to consult with lecturers about learning activities. The recommendations of this study are aimed at Academic Advisors, UPT LBK, Study Programs, and further researchers.